Effect of the WeChat Platform Health Management and Refined Continuous Nursing Model on Life Quality of Patients with Acute Myocardial Infarction after PCI. (29th November 2021) - Xu, Meifang; Yang, Xiaofang; Liu, Lin; Dai, Yunlang; Xu, Mingzhu; Lin, Shi
Abstract : The purpose was to explore the effect of the WeChat platform health management and refined continuous nursing model on life quality of patients with acute myocardial infarction (AMI) after PCI. 100 AMI patients treated in the cardiovascular medicine of the First Affiliated Hospital of Soochow University from June 2018 to June 2019 were selected as the study subjects and randomly divided into research group and reference group, with 50 cases in each group. The reference group received routine nursing after PCI, while the research group received WeChat platform health management and continuous refined nursing. There were no significant differences in sex ratio, age, BMI, complications, education level, and residence between the two groups of patients (P > 0.05 ). The MPR values of patients in the two groups after intervention were significantly higher than those before intervention (P < 0.05 ), and the MPR value in the research group after intervention was significantly higher than that in the reference group (P < 0.05 ). The SF-36 scores of patients in the two groups after intervention were significantly higher than those before intervention (P < 0.001 ), and the SF-36 score in the research group after intervention was higher than that in the reference group (P < 0.001 ). The emotional, physical, and economic dimensions of patients in the research group after intervention were significantly lower than those in the reference group (P < 0.001 ). The HAMA and HAMD scores of patients in the research group after intervention were significantly lower than those in the reference group (P < 0.001 ). The nursing satisfaction score of patients in the research group was significantly higher than that in the reference group (P < 0.001 ). The total incidence of complications of patients in the research group after intervention was significantly lower than that in the reference group (P < 0.05 ). The WeChat platform health management and refined continuous nursing model can effectively improve the medication compliance of patients after PCI, improve the life quality, alleviate depression and anxiety, and reduce postoperative complications, with a definite effect, which is worthy of promotion and application.